Client’s Attitude Regarding Antibiotics Misuse in Primary Health Care Centers - Alia’a Neamah Abo Alshon1, Naji Yaser Almiahi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Antibiotics are powerful drugs that fight some infections and can save lives when used properly. It either stops the bacteria from multiplying or destroying them. Objectives: The study aims to: 1. Evaluate the client’s position regarding the abuse of antibiotics in primary health care centers. 2. Identification of relationships of abuse of antibiotics and social demographics (age, sex, place of residence, level of education, economic status, profession, marital status). Methods: A descriptive study (quantitative design) was carried out using a cross-sectional design to study the assessment of the client’s position on the misuse of antibiotics in primary health care centers in Diwaniya from July 2018 to July 2019 .A sample of 450 female clients and 221 women in primary health care centers in Diwaniyah (Al Jazira Health Center, Al Talea Health Center, Al Taqia Health Center, New Health Center, Al Furat Health Center) The questionnaire was created through a comprehensive review of available literature and related studies. Results: The results of the study show that the clients do not agree with the negative attitude regarding the misuse of antibiotics. Therefore, the study reveals a relationship between the social demographic and the second part. The result shows that there is a very large relationship between all elements of the second part with age, Educational level, economic status, occupation, social status. While there is little correlation with gender and place of residence